Exploring the lived experiences of culturally and linguistically diverse caregivers of students in virtual learning environments - Loya Thiess, Laura (My University, 2025)
This qualitative phenomenological study explored the lived experiences of culturally and linguistically diverse (CLD) caregivers of general education students enrolled in kindergarten through eighth grade virtual school settings in Texas. The purpose of the study was to understand how caregivers navigated communication systems, instructional expectations, and technology demands in online learning environments. Data were gathered through a demographic and technology survey, semi-structured interviews, voluntary focus group discussion, and document review with six CLD Latinx, Spanish-speaking caregivers whose experiences reflected diverse educational and family contexts. Guided by Cultural-Historical Activity Theory (CHAT) and Biography-Driven Culturally Responsive Teaching (BDCRT), data were analyzed using an interpretive phenomenological approach to uncover recurring patterns of meaning. Five major themes emerged: virtual learning as a source of safety and empowerment; language functioning as both a challenge and a tool; parents as learning coaches, translators, co-teachers, and advocates; school disorganization and inconsistent communication; and the need for greater cultural responsiveness and comprehensive support. Across themes, the findings revealed tensions between the intended design of virtual schooling and the lived realities of families. Caregivers responded with advocacy, cultural knowledge, and technological problem-solving to bridge systemic gaps and sustain their children’s learning. These adaptations reflected both resilience and the need for greater institutional empathy. Ultimately, the study underscores the importance of culturally responsive, linguistically accessible, and emotionally attuned virtual education practices that promote equity and authentic collaboration for CLD families.
Keywords: Parent engagement; Virtual education; Culturally and linguistically diverse parent engagement; School-family partnerships